The Use of Two DPM Modes Equipped with a Thermohygrometer and Pressure Selection for the Implementation of Community Service - Syaifudin Syaifudin; Ketut Dyah Kusumawati; Tribowo Indrato (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Calibration is a technical activity consisting of determination, determination of one or more properties and characteristics of a product, process,s or service in accordance with a specific procedure that has been determined. The purpose of calibration is to ensure that the measurement results comply with national and international standards. Digital Pressure Meter (DPM) Two Modes equipped with Thermohygrometer and Pressure Selection is a device used to determine positive pressure and negative pressure (vacuum). Using the MPX 5050GP sensor as a positive pressure sensor. maximum pressure requirement is 300 mmHg. Using a DHT 22 sensor for temperature humidity. This device is also equipped with a leak test timer. The display used in this module is a 2.4-inch TFT Nextion LCD. After carrying out the measurement process to the mercury sphygmomanometer 6 times, the smallest result was 0 mmHg at 0 mmHg pressure and the largest was 298.0 mmHg at 300mmHg pressure. Based on the temperature humidity data collection carried out in the room obtained 31̊C at temperature and 87% at humidity.